Growth and Degradation Kinetics of Organic–Inorganic Hybrid Perovskite Films Determined by In Situ Grazing‐Incidence X‐Ray Scattering Techniques. Issue 12 (5th November 2021) - Wang, Jian; Wang, Weijia; Chen, Yonghua; Song, Lin; Huang, Wei
Abstract: Organic–inorganic halide perovskite (OIHP) solar cells hold a great promise for commercial breakthrough since their power conversion efficiency has been pushed beyond the mark of 25%, making them capable of competing with traditional crystalline silicon solar cells. The key to achieve efficient and stable perovskite solar cells is inherently related to the film morphology. The understanding of the kinetic processes of film formation and degradation opens up possibilities to tailor the film morphology via the regulation of precursor and processing parameters. In situ grazing‐incidence X‐ray scattering (GIXS) techniques allow for tracking the morphology evolution of thin films at different length scales and with high temporal resolution. In this review, the selected examples for application of in situ grazing‐incidence wide‐angle X‐ray scattering and grazing‐incidence small‐angle X‐ray scattering techniques to the growth and stability of OIHPs are summarized after a brief introduction to both techniques, highlighting particularly the morphological evolution of perovskite films over time. Then the correlated mathematical models are reviewed to give a toolbox for analyzing the mechanisms of film formation and degradation. Thus, an overview on the in situ GIXS methods is linked to the research of OIHP kinetics. Abstract : This review systematically introduces the advances in determining the growth and degradation kinetics of organic–inorganic hybrid perovskite films by in situ grazing‐incidence X‐ray scattering techniques. The advanced techniques are able to reveal the structure evolution in real time during film formation and under aging conditions, which is helpful to establish and perfect the mechanism of perovskite growth and degradation.